2011
DOI: 10.1007/s00248-011-9857-0
|View full text |Cite
|
Sign up to set email alerts
|

Prodigiosin from Vibrio sp. DSM 14379; A New UV-Protective Pigment

Abstract: Pigments such as melanin, scytonemin and carotenoids protect microbial cells against the harmful effects of ultraviolet (UV) radiation. The role in UV protection has never been assigned to the prodigiosin pigment. In this work, we demonstrate that prodigiosin provides a significant level of protection against UV stress in Vibrio sp. DSM 14379. In the absence of pigment production, Vibrio sp. was significantly more susceptible to UV stress, and there was no difference in UV survival between the wild-type strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 63 publications
1
42
0
3
Order By: Relevance
“…The bacteria that do not have such homologues are prodigiosin sensitive. Prodigiosin as an antibacterial agent has high potential in biotechnological and medical applications [411], as well as in microbial ecology due to its ability to modulate bacterial ecophysiology [12,1719]. It was shown that prodigiosin impregnated to cellulose matrix effectively removes E .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacteria that do not have such homologues are prodigiosin sensitive. Prodigiosin as an antibacterial agent has high potential in biotechnological and medical applications [411], as well as in microbial ecology due to its ability to modulate bacterial ecophysiology [12,1719]. It was shown that prodigiosin impregnated to cellulose matrix effectively removes E .…”
Section: Introductionmentioning
confidence: 99%
“…coli is not known, the conflicting data of prodigiosin antibacterial action are difficult to reconcile. As several ecopysiological roles of prodigiosin have been proposed for bacteria such as air dispersal of bacteria [24], metabolic sink for NAD(P)H or proline [25], storage of light energy [17], anion exchange [18], energy spilling function [26] and UV protection [19], it is possible that antimicrobial activity is not the result of prodigiosin aiming at a single cell target, but in turn may have a pleiotropic effect on E . coli physiology.…”
Section: Introductionmentioning
confidence: 99%
“…This red pigment can be produced by S. marcescens and other microorganisms, such as Zooshikella rubidus, Vibrio sp., Streptomyces griseoviridis, and Hahella chejuensis (Lewis and Corpe, 1964;Song et al 2006;Huh et al 2007;Alihosseini et al 2008;Kawasaki et al 2008;Kim et al 2008;Borić et al 2011;Lee et al 2011). Prodigiosin has great potential for clinical and environmental application owing to its reported characteristics of having anti-fungal, anti-bacterial, anti-protozoal/anti-malarial, immunosuppressive, and antiproliferative activity (Williamson et al 2005).…”
Section: Introductionmentioning
confidence: 96%
“…9 The red-pigmented prodiginines are bioactive secondary metabolites produced by microorganisms like Serratia marcescens and Vibrio sp. 10 These pigments are known to possess immunosuppressive and anticancer properties. 11 Prodigiosin have potential applications in textiles, cosmetics, etc.…”
Section: Introductionmentioning
confidence: 99%